A Tissue-Tended Mycophenolate-Modified Nanoparticle Alleviates Systemic Lupus Erythematosus in MRL/Lpr Mouse Model Mainly by Promoting Local M2-Like Macrophagocytes Polarization - Jiang B; Zhang Y; Li Y; Chen Y; Sha S; Zhao L; Li D; Wen J; Lan J; Lou Y; Su H; Zhang C; et al. (International Journal of Nanomedicine, 2022)
Biling Jiang,1,* Yamin Zhang,1,* Yuce Li,2 Yu Chen,2 Shanshan Sha,1 Liang Zhao,1 Danqi Li,1 Jingjing Wen,1 Jiajia Lan,1 Yuchen Lou,1 Hua Su,3 Chun Zhang,3 Jintao Zhu,2 Juan Tao1 1Hubei Engineering Research Center of Skin Disease Theranostics and Health, Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology (HUST), Wuhan, People’s Republic of China; 2Hubei Engineering Research Center for Biomaterials and Medical Protective Materials, School of Chemistry and Chemical Engineering, HUST, Wuhan, People’s Republic of China; 3Department of Nephrology, Union Hospital, Tongji Medical College, HUST, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juan Tao; Jintao Zhu, Email tjhappy@126.com; jtzhu@mail.hust.edu.cnBackground: Mycophenolate mofetil (MMF), for which the bioactive metabolite is mycophenolic acid (MPA), is a frequently used immunosuppressant for systemic lupus erythematosus (SLE). However, its short half-life and poor biodistribution into cells and tissues hinder its clinical efficacy. Our dextran mycophenolate-based nanoparticles (MPA@Dex-MPA NPs) have greatly improved the pharmacokinetics of MMF/MPA. We here tested the therapeutic efficacy of MPA@Dex-MPA NPs against SLE and investigated the underlying mechanism.Methods: The tissue and immune cell biodistributions of MPA@Dex-MPA NPs were traced using live fluorescence imaging system and flow cytometry, respectively. Serological proinflammatory mediators and kidney damage were detected to assess the efficacy of MPA@Dex-MPA NPs treatments of MRL/lpr lupus-prone mice. Immune cell changes in the kidney and spleen were further analyzed post-treatment via flow cytometry. Bone marrow-derived macrophages were used to investigate the potential mechanism.Results: MPA@Dex-MPA NPs exhibited superior therapeutic efficacy and safety in the MRL/lpr mice using significantly lower administration dosage (one-fifth) and frequency (once/3 days) compared to MMF/MPA used in ordinary practice. The overall prognosis of the mice was improved as they showed lower levels of serological proinflammatory mediators. Moreover, kidney injury was alleviated with reduced pathological signs and decreased urine protein-creatinine ratio. Further investigations of the underlying mechanism revealed a preferential penetration and persistent retention of MPA@Dex-MPA NPs in the spleen and kidney, where they were mostly phagocytosed by macrophages. The macrophages were found to be polarized towards a CD206+ M2-like phenotype, with a downregulation of surface CD80 and CD40, and reduced TNF-α production in the spleen and kidney and in vitro. The expansion of T cells was also significantly inhibited in these two organs.Conclusion: Our research improved the efficacy of MPA for MRL/lpr mice through synthesizing MPA@Dex-MPA NPs to enhance its tissue biodistribution and explored the possible mechanism, providing a promising strategy for SLE therapy.Graphical Abstract: Keywords: mycophenolate, nanoparticles, macrophage polarization, tissue damage, systemic lupus erythematosus